Perceived exertion reflects fatigue conditions during power-aimed resistance training - Zhao, Hanye; Kurokawa, Takanori; Tajima, Masayoshi; Liu, Zijian; Okada, Junichi (International Journal of Sports Medicine, 2025)
Fatigue is an inevitable part of resistance training, making its monitoring crucial to prevent performance decline. This study evaluated the validity of ratings of perceived exertion as a measure of fatigue during power bench press exercises. Fourteen sub-elite male athletes completed three bench press tasks with varying volumes (low, medium, and high) at 65% of their one-repetition maximum. The rating of perceived exertion, a spectral fatigue index, and velocity loss were measured across all conditions. Significant effects were observed for the overall ratings of perceived exertion, average velocity loss, and average spectral fatigue index (all p<0.001). As tasks progressed, the rating of perceived exertion and the spectral fatigue index increased significantly (p<0.001), while the velocity loss was not significant under the low-volume condition. Significant correlations were found between the rating of perceived exertion and the spectral fatigue index (r=0.547, p<0.001), the velocity loss and the spectral fatigue index (r=0.603, p<0.001), and the rating of perceived exertion and the velocity loss (r=0.667, p<0.001). The findings suggest that both the rating of perceived exertion and the velocity loss are valid measures of fatigue in power bench press exercises. However, the rating of perceived exertion is a more practical option due to its simplicity and accessibility. Furthermore, the rating of perceived exertion can act as a substitute for velocity when measurement tools are unavailable. It should be noted that velocity alone may not fully capture fatigue in low-repetition power training.
Keywords: borg scale; neuromuscular fatigue; resistance training; surface electromyography